DSP based overcurrent relay using fuzzy bang-bang controller - Goh Y.L.; Ramasamy A.K.; Nagi F.H.; Abidin A.A.Z. (2023)
Overcurrent relays are very important protection component that require high reliability to maintain high security in power systems. With the new numerical relay technology using digital signal processor (DSP), it is possible to improve the performance of the relay significantly. However, application of DSP in numerical overcurrent relays is limited especially in coordination among the group of relays. The relay must work proficiently to coordinate with the networks in order to avoid mal-operation. Therefore, in this paper, an implementation of overcurrent relay with improved coordination on a DSP, TMS320F2812 is described. The fuzzy bang-bang controller is used as the control strategy for the relay to provide efficient control for overcurrent protection. The performance evaluation of the proposed system is based on steady state analysis, transient state analysis, coordination and lastly the execution time of the DSP. The results obtained using this new proposed controller is very promising. 2011 Elsevier Ltd. All rights reserved.